Effect of low-level laser therapy on postoperative endodontic pain: An updated systematic review - Marcella Yasmin Reis Guerreiro; Laise Pena Braga Monteiro; Roberta Fonseca de Castro; Marcela Baraúna Magno; Lucianne Cople Maia; Juliana Melo da Silva Brandão (Elsevier, 2021)
Objective: To evaluate the influence of low-level laser therapy (LLLT) on postoperative pain after endodontic treatment. Methods: The PICOS strategy was used to identify randomized clinical trials comparing low-level laser therapy and mock laser therapy to manage postoperative pain after endodontic treatment, retreatment, and endodontic surgery. An electronic search was performed in MEDLINE through PubMed, Web of Science, LILACS, Scopus and Cochrane Library, OpenGrey and Google Scholar. Quality assessment was performed using the Cochrane Collaboration's tool for assessing the risk of bias. The quality of evidence was rated on the basis of the GRADE approach. Results: Twelve studies were included in the qualitative synthesis. Within the 12 studies, 7 articles were classified as "low risk of bias," 4 studies were considered "unclear risk of bias" and 1 study was considered ''high risk of bias.'' Six studies evaluated the postoperative pain after primary root canal treatment, two studies after root canal retreatment and four after periapical surgery. Most of the studies reported significantly less postoperative pain after LLLT in different time periods; two studies found no differences. The certainty of evidence was classified as low and very low to treatment / retreatment and endodontic surgery, respectively. Conclusions: Based on the limited quality evidence, most of the included studies reported significantly less postoperative pain after LLLT. However, the lack of standardization in laser parameters, use of medications and the certainty of evidence classified as low and very low indicate the need for further studies.